Recent advances in surface modification of micro- and nano-scale biomaterials with biological membranes and biomolecules - Abesekara, Manisha Sandupama; Chau, Ying (Frontiers in Bioengineering and Biotechnology, 2022)
Surface modification of biomaterial can improve its biocompatibility and add new biofunctions, such as targeting to specific tissues, communication with cells, and modulation of intracellular trafficking. Here, we summarize the use of various natural materials, namely cell membrane, exosomes, proteins, peptides, lipids, fatty acids, and polysaccharides as coating materials on micron-sized and nano-sized particles and droplets with the functions imparted by coating with different materials. We discuss the applicability, operational parameters and limitation of different coating techniques, from the more conventional approaches such as extrusion and sonication to the latest innovation seen on the microfluidic platform. Methods commonly used in the field to examine the coating, including its composition, physical dimension, stability, fluidity, permeability, and biological functions are reviewed.